Reduction of the self-dual Yang-Mills equations I. Poincaré group - Fushchich, V. I.; Lagno, V. I.; Zhdanov, R. Z. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
For the vector potential of the Yang-Mills field, we give a complete description of ansatzes invariant under three-parameterP (1, 3) -inequivalent subgroups of the Poincaré group. By using these ansatzes, we reduce the self-dual Yang-Mills equations to a system of ordinary differential equations.